If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x(5 + 4) = 3x + 2 Combine like terms: 5 + 4 = 9 5x(9) = 3x + 2 Reorder the terms for easier multiplication: 5 * 9x = 3x + 2 Multiply 5 * 9 45x = 3x + 2 Reorder the terms: 45x = 2 + 3x Solving 45x = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 45x + -3x = 2 + 3x + -3x Combine like terms: 45x + -3x = 42x 42x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 42x = 2 + 0 42x = 2 Divide each side by '42'. x = 0.04761904762 Simplifying x = 0.04761904762
| 6x+1-(x-7)=6-2(5-4x) | | z^2-4=iz^2-2iz-8i | | 8*15=10(x+15) | | 3x-1=13-x | | 3.556-1.48= | | -4(2x-3x)=2(3x-4)+6x | | X^2-38=11 | | 3(5x+6)-6=15x+12 | | (4Y+2X-1)dx+(6y+4x-5)dy=0 | | 4x-y+z=0 | | 5h-1=7-h-2 | | 2(x+1)+5=4x-6 | | 14v=7v+56 | | (2-2i)*(8+3i)= | | Y=1+2(10) | | 6+8m=16 | | 3.55-1.48= | | -2m+6=-m | | 2p=-9(p+11) | | Y=1+2(5) | | F(-5)=2x+8 | | 3u-3=8u-8 | | Y=1+2(4) | | 4x+6-x=-12 | | 4g=36.3 | | Y=1+2(2) | | -28=3x+8 | | 3tanx^2-2tanx+1=0 | | (5y+6)-(2+4y)=5 | | -3x+4+4x=15-34 | | 5/x=6/12 | | 8j=9j-8 |